2023
DOI: 10.3390/s23136017
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assessment of the 2-Minute Walk Distance for Remote Monitoring of People with Multiple Sclerosis

Abstract: The aim of this study was to investigate the feasibility of automatically assessing the 2-Minute Walk Distance (2MWD) for monitoring people with multiple sclerosis (pwMS). For 154 pwMS, MS-related clinical outcomes as well as the 2MWDs as evaluated by clinicians and derived from accelerometer data were collected from a total of 323 periodic clinical visits. Accelerometer data from a wearable device during 100 home-based 2MWD assessments were also acquired. The error in estimating the 2MWD was validated for wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Second, concerning the P6MC, previous studies have shown that this could be aggregated as an unsupervised 6 min walking test. However, we cannot be sure that the activity was walking [ 38 , 72 ]. However, the cumulative step count over the 6-min duration provides valuable information about participants’ endurance and functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, concerning the P6MC, previous studies have shown that this could be aggregated as an unsupervised 6 min walking test. However, we cannot be sure that the activity was walking [ 38 , 72 ]. However, the cumulative step count over the 6-min duration provides valuable information about participants’ endurance and functional capacity.…”
Section: Discussionmentioning
confidence: 99%